2015
DOI: 10.1136/emermed-2015-204926
|View full text |Cite
|
Sign up to set email alerts
|

An external validation study of a clinical prediction rule for medical patients with suspected bacteraemia

Abstract: ObjectiveThe objective of this study was to externally validate a clinical prediction rule (CPR)—the ‘Shapiro criteria’—to predict bacteraemia in an acute medical unit (AMU).MethodsProspectively collected data, retrospectively evaluated over 11 months in an AMU in the UK. From 4810 admissions, 635 patients (13%) had blood cultures (BCs) performed. The 100 cases of true bacteraemia were compared with a randomly selected sample of 100 control cases where BCs were sterile.ResultsTo predict bacteraemia (at a cut-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
(32 reference statements)
0
13
1
8
Order By: Relevance
“…Some studies include chills as a variable and show that 14–95% of patients with bacteremia and 9–75% of patients without bacteremia have chills [3, 4, 6, 11, 13, 15, 22, 30, 31]. The reason for this very large variation may be that the data usually derives from retrospectively reviewing clinical admission notes.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies include chills as a variable and show that 14–95% of patients with bacteremia and 9–75% of patients without bacteremia have chills [3, 4, 6, 11, 13, 15, 22, 30, 31]. The reason for this very large variation may be that the data usually derives from retrospectively reviewing clinical admission notes.…”
Section: Discussionmentioning
confidence: 99%
“…Other well-studied clinical predictive models are the SIRS criteria (systemic inflammatory response syndrome) and the Shapiro criteria (11, 12) (see Figure 2). Both these models have demonstrated high sensitivity but low specificity (1416) and rely on laboratory parameters that are not readily available in most LMICs. Their usefulness in daily practice is therefore rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they concluded that for low-risk patients BC analysis might be omitted. In independent external validation studies, this rule resulted in similar ROC-AUCs 34 , 35 . Several similar scores and modifications of the Shapiro score have been established, resulting in a similar outcome 36 39 .…”
Section: Discussionmentioning
confidence: 78%